Transplantation’s Greatest Challenges: Advances in Chronic Graft-versus-Host Disease - Warren D. Shlomchik; Stephanie J. Lee; Daniel R. Couriel; Steven Z. Pavletic (2007)
Clinical research into chronic graft-versus-host disease (GVHD) lags behind that in other areas in the field. Interest in chronic GVHD has increased significantly in recent years for various reasons, including advances in biotechnology, a perceived increase in the incidence of chronic GVHD, and decreased regimen-related mortality, resulting in a new emphasis on quality of life and absence of disability as endpoints of major significance in transplantation survivors. In this overview, we address 3 key areas related to chronic GVHD that hold the highest promise for major advances in the near future: pathobiology, response criteria, and therapy.